Noun phrases in Creole languages : a multi-faceted approach - Baptista, Marlyse; Guéron, Jacqueline (Creole language library ;, 2007)
This volume offers a thorough examination of the syntactic, semantic, pragmatic and discourse properties of noun phrases in a wide variety of creole (and non-creole) languages including Cape Verdean Creole, Santome, Papiamentu, Guinea-Bissau Creole, Mindanao Chabacano, Réunionnais Creole, Lesser Antillean, Haitian Creole, Mauritian Creole, Seychellois, Sranan, Jamaican Creole, Berbice Dutch Creole and African American English. Comparative studies also consider the determiner systems of Middle and Modern French, European Portuguese, Brazilian Portuguese, Spanish, Ewe, Fon and Gun. This compilat.